Production and Distribution of Durian (Durio Zibethinus Murr.) in Wonosalam, Jombang - Djuhari Djuhari; Siti Muslikah; Lia Rohmatul Maula; Rose Novita Sari Handoko (Postgraduate School Universitas Brawijaya, 2021)
The pattern of durian planting in the community, in general, uses the agroforestry pattern so that in one area of land there is more than one annual crop cultivated (multiple cropping). However, there is no distribution data map and its production potential. Research on mapping and potential of durian production in Wonosalam district is needed as an effort to provide data-based and to develop durian crop farming. The purpose of this study is to map the distribution of plants and the potential for durian production in the Wonosalam sub-district, Jombang district. The research is descriptive with surveys, observation, and in-depth interview methods. Farmer respondents were taken by